Millennial-scale fluctuations in water volume transported by the Tsushima Warm Current in the Japan Sea during the Holocene - Horikawa, Keiji; Kodaira, Tomohiro; Ikehara, Ken; Murayama, Masafumi; Zhang, Jing (Global and Planetary Change, 2019)
Cyclic changes in volume transport of the Tsushima Warm Current (TWC) have been argued from diatom records in the southern Japan Sea off the Japanese islands during the Holocene. Although this phenomenon has not yet been confirmed by various proxy data, determining whether or not these oceanographic changes occurred is crucial for clarifying the nature of oceanographic changes in the southern Japan Sea. Here, we conducted a coupled analysis of Mg/Ca ratios and oxygen isotopes (δ18O) in shallow-dwelling Neogloboquadrina incompta from 13 core-top sediments in southern Japan, and developed a new equation for Mg/Ca temperature calibration (Mg/Ca = 0.311 × exp (0.07 × T)) as a proxy for spring sea surface temperature (SST). Using the newly developed, species-specific Mg/Ca-paleothermometry, we reconstructed SST variability for the past 6800 years from core YK10-7-PC09 in the southern Japan Sea. The Mg/Ca-derived SST record clearly represented five warmer periods at 6200–6000, 4900–4500, 4200–3800, 2600–2100, and 900–400 cal. year BP, almost consistent with previously published diatom records. These warmer events also corresponded to the periods in which warm molluscan assemblages increased at the northern end of the TWC, suggesting that periods of higher SST can be seen as reflecting the increased volume transport of the TWC. We interpreted the results of a model study showing that higher solar irradiance provoked positive Arctic Oscillation (AO)-like spatial patterns and the negative phase of the Pacific Decadal Oscillation (PDO) to mean that increased (reduced) TWC volume transport on the multi-centennial to millennial time scales was caused by high (low) solar insolation via a potential link between AO and PDO. Given that larger and more frequent volcanic eruptions occurred in the mid Holocene than in the late Holocene, volcanic forcing on the TWC volume transport changes would have been more significant during the former, as seen in the highly variable SST from this period and distinct decreases in SST around ~5900 cal. year BP and ~6400 cal. year BP. The millennial-scale fluctuations seen in SSTs in the southern Japan Sea would have had a large impact on the evolution of vegetation and human adaptation in the northern Japanese islands, adjacent to the Japan Sea, over the last 6800 years.
Keywords: Holocene; Mg/Ca-derived; Neogloboquadrina incompta; sea-surface temperature; Solar forcing; The Japan Sea; Tsushima; Warm Current